PEREMPUAN-PEREMPUAN DI PASAR ANGSO DUO 1974-2018 - Nuryani, Windi; Syaputra ZE, Deki (Universitas Batanghari Jambi, 2022)
Angso Duo Market is one of the largest Traditional Markets in Jambi City, the buildings in this market have been revitalized or renovated. Merchants at the Angso Duo Market distribute goods to earn income, the income received by traders every day is uncertain. This study aims to, one how the existence of women in the Angso Duo market and, two how female traders carry out their activities as traders and as housewives. exercise his or her own judgment in selecting traders to participate in this study. This research was conducted at the Angso Duo Baru Market, Jambi City in August 2021 to October 2021. The results of this study indicate that simultaneously knowing the development of the number of traders from year to year, the comparison between female and male traders, education level, types of merchandise , the role of women traders, the contribution of women traders to family income, the role of women traders in socio-economic life, the allocation of women's working time.